Tuberculin testing in two Liverpool social clubs: the effects of a tuberculosis outbreak on background positivity. Issue 6 (June 1996) - Syed, Q; Bellis, M A; Beeching, N J; Tocque, K; Williams, C S; Jamieson, S; Steele, A; Davies, P D
Abstract : BACKGROUND: Tuberculin testing remains the standard method for assessing infection due to tuberculosis in the UK. However, there are no data on the incidence of tuberculin positivity among the general adult population in the UK and consequently interpretation of Heaf test results is often difficult. METHODS: During the investigation of an outbreak of tuberculosis in a Liverpool social club 198 members were interviewed and Heaf tested and 171 members of a second social club in Liverpool were similarly screened as a control group. Comparisons between the results from the two populations provided both an estimate of baseline Heaf test positivity in indigenous white adults from a British inner city population, and a measure of the effect on this baseline of recent exposure to tuberculosis. RESULTS: In both club populations the proportion of positive Heaf tests increased with age. Independent of age, the tuberculosis exposed population had a higher proportion of positive Heaf grade results (40.9%) than those in the control group (26.9%). Multivariate analysis confirmed both the differences in Heaf results between clubs and between age groups but identified no other behavioural or medical factors which affected Heaf test results. CONCLUSIONS: Heaf test positivity increases with age at least up to 54 years, and recent exposure to tuberculosis increases the proportion of positive Heaf tests in each age group. Interpretation of positive Heaf tests when assessing the effects of a tuberculosis outbreak should take account of background levels of Heaf positivity.